Relationship Between Anemia and Outcomes of Covid-19 Patients at Yarsi Hospital for The Period of June 2020 – June 2022 - Hermi, Permata; Hasibuan, Faizal Drissa; Arifandi, Firman (Fakultas Kedokteran Universitas YARSI, 2025)
Introduction: Anemia and COVID-19 share a complex relationship. Several published studies have yet to conclusively determine the relationship between anemia and COVID-19 outcomes. Given the importance of the inflammatory process associated with COVID-19 and its role in the pathogenesis of anemia, further research is needed to evaluate the relationship between anemia and COVID-19 patient outcomes. Methods: This study is a quantitative and qualitative analytical study using a cross-sectional approach. The data analyzed is secondary data from the Electronic Medical Record of YARSI Hospital, covering the period from June 2020 to June 2022. The relationship between variables was analyzed using the Wilcoxon Signed Ranks Test, Spearman’s correlation test, and Pearson’s correlation test. Results: A total of 242 patients met all inclusion criteria. Of these, 100 patients were in the anemia group and 142 in the non-anemia group. Statistical analysis revealed a significant difference in the length of hospital stay for COVID-19 patients with anemia compared to those without anemia (Z score -13.3415), with anemic patients having a longer stay. Additionally, the anemia group showed a better recovery rate than the non-anemic group (Z score −11.136). A nonsignificant negative relationship was also found between anemia and COVID-19 severity (Spearman’s rho -0.105, p=0.300). Hemoglobin levels had a nonsignificant negative correlation with the length of hospital stay (Pearson correlation coefficient -0.104, p=0.107). Conclusion: COVID-19 patients with anemia in this study showed better recovery outcomes compared to non-anemic patients but had longer hospital stays.